Disentangling 'the social' in social design's engagement with the public realm. Issue 3 (3rd July 2017) - Markussen, Thomas
Abstract: Co-Design's increasing engagement with the public realm is closely related to the widespread turn towards 'the social' in design and design research. However, there is a lack of understanding of how the notion of the social in social design differs from social innovation and social entrepreneurship. This paper provides an inter-disciplinary examination of research literature with the purpose of positioning social design more firmly in its difference from these other approaches. One of the tangible results is an analytical framework that enables design researchers to grasp what is unique to social design and wherein lies the value for the public realm. By developing a set of defining criteria such as aim, modus operandi, social value, locus of design and innovation, and the scale of effects, the paper offers a fine-grained disentangling of the social in social design.